Preparation method and application of carbon nanotube and nitrogen-doped porous carbon supported monatomic copper catalyst
By performing nitrogen doping on the carbon support and forming a core-shell structure, a high-activity and high-stability carbon nanotube @ nitrogen-doped porous carbon-supported single-atom copper catalyst was prepared, which solved the problems of low activity and poor stability of existing catalysts. , high-efficiency catalysis in methanol liquid phase oxidation carbonylation reaction is achieved.
Patent Information
- Application Number
- CN202310950015.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-14
AI Technical Summary
The existing carbon-supported copper catalysts have problems of low activity and poor stability in methanol liquid-phase oxidation carbonylation reaction, and the aggregation of Cu nanoparticles affects the performance of the catalyst.
The catalyst was prepared by hydrothermal reaction and pyrolysis treatment using carbon nanotube @nitrogen doped porous carbon-supported single-atom copper catalyst to form a core-shell structure to reduce internal diffusion and improve catalytic activity.
It significantly improves the activity and stability of the catalyst, enhances the utilization rate and electronegativity of copper atoms, reduces environmental pollution during the catalyst preparation process, and is suitable for industrial applications.
Smart Images

Figure CN119425751A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst preparation, and in particular to a method for preparing a carbon nanotube@nitrogen-doped porous carbon-supported single-atom copper catalyst and its application in liquid methanol oxidative carbonylation reaction. Background Art
[0002] Dimethyl carbonate is a "green" chemical product with high added value. It can replace highly toxic and carcinogenic phosgene and dimethyl sulfate as a methylation agent, carbonylation agent, etc. to manufacture many high value-added chemical products. It has many uses in organic synthesis, medicine, pesticides, solvents, fuel additives, etc. The industrial preparation methods of dimethyl carbonate include phosgene method, ester exchange method and oxidative carbonylation method (including liquid phase method and gas phase method). Among them, the oxidative carbonylation method is a reaction using methanol, oxygen and carbon monoxide under the action of a catalyst. The process has the characteristics of cheap and easy-to-obtain raw materials, simple process and low cost. The catalyst is the key to the reaction.
[0003] The Italian Eni Chem company first developed the CuCl catalytic system and took the lead in industrializing the process of synthesizing dimethyl carbonate by liquid-phase oxidation carbonylation of methanol in the mid-1980s. However, the solubility of CuCl in methanol is poor, the reaction efficiency is low, the chloride ions are highly corrosive to the stainless steel reactor, and the catalytic system has the problem that the catalyst is not easy to separate and recycle. In order to solve the above problems, patent applications CN111974435A, CN107262095A, CN105293484A, CN104324757A, etc. prepared a series of carbon-supported nano-copper catalysts. However, since copper exists in particles and the agglomeration of Cu nanoparticles during the reaction process seriously affects the activity and stability of this type of catalyst; in addition, current research mainly improves the diffusion of the catalyst by adjusting the pore size of the carbon material, and the adjustment method is single and the activity improvement is limited; the above factors hinder the industrialization process of carbon-supported copper catalysts.
[0004] The present invention attempts to prepare a carbon-supported single-atom copper catalyst and nitrogen-dope the carbon support to improve the stability and activity of the copper species. At the same time, the porous carbon is coated on the outer layer of the carbon nanotube to form a core-shell structure; the carbon nanotube @ nitrogen-doped porous carbon-supported single-atom copper core-shell structure is used to reduce the internal diffusion of the catalyst and further improve its catalytic activity, thereby fundamentally solving the problems of low activity and poor stability in current catalysts. Summary of the invention
[0005] In view of the problems existing in the above-mentioned prior art, the purpose of the present invention is to provide a highly active and stable carbon nanotube@nitrogen-doped porous carbon-supported single-atom copper catalyst for the liquid-phase oxidative carbonylation of methanol to synthesize dimethyl carbonate and a preparation method thereof.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] A carbon nanotube@nitrogen-doped porous carbon-supported single-atom copper catalyst, the specific preparation method of which comprises the following steps:
[0008] A certain amount of organic solvent and deionized water are added to a hydrothermal reactor, a certain amount of 5,5-divinyl-2,2-bipyridine copper complex, vinyl imidazole bromide, and azobisisobutyronitrile (AIBN) are added to the obtained mixed solution, and after stirring and dissolving completely, a certain amount of multi-walled carbon nanotubes are added, and stirring is continued for 30 minutes; then, the reactor is sealed, and the reactor is transferred to a forced air drying oven, and the polymerization reaction is carried out at 80-140° C. for 12-48 hours. After cooling to room temperature, the obtained solid is washed with anhydrous ethanol for 3-5 times, and then vacuum dried to obtain a nitrogen-containing porous polymer@carbon nanotube composite material;
[0009] The obtained nitrogen-containing porous polymer@carbon nanotube composite material is placed in a tube furnace, and under the protection of inert gas, the temperature is programmed to 550-700°C at a heating rate of 1-5°C / min for pyrolysis, the pyrolysis is performed for 1-4 hours, and the carbon nanotube@nitrogen-doped porous carbon-supported single-atom copper catalyst is obtained.
[0010] Furthermore, the structural formula of the 5,5-divinyl-2,2-bipyridine copper complex is as follows:
[0011]
[0012] In the structural formula, Cu is +1 or +2, and X is Cl. - Br - ,I - 、CH3COO - Any one of, CuX is preferably any one of CuCl, CuBr, CuI, CuCl2, CuBr2, Cu(CH3COO)2, more preferably one of CuCl and CuBr.
[0013] Further, the vinyl imidazole bromide is any one of V2Br, V3Br, and V6Br, and its structure is as follows:
[0014]
[0015] Preferably, the vinyl imidazolium bromide is V2Br or V6Br, more preferably V2Br.
[0016] Furthermore, the organic solvent is one of N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone.
[0017] Furthermore, the ratio of the mass of the multi-walled carbon nanotubes to the total mass of the monomers 5,5-divinyl-2,2-bipyridine copper complex and vinyl imidazole bromide is 1:(1-10), preferably 1:(4-6), and more preferably 1:5.
[0018] Furthermore, the multi-walled carbon nanotube has an inner diameter of 2-20nm, an outer diameter of 6-80nm, and a length of 0.5-30μm. Preferably, the multi-walled carbon nanotube has an inner diameter of 5-15nm, an outer diameter of 10-20nm, and a length of 0.5-2μm. More preferably, the multi-walled carbon nanotube has an inner diameter of 5-10nm, an outer diameter of 10-20nm, and a length of 0.5-2μm.
[0019] Furthermore, the mass ratio of the 5,5-divinyl-2,2-bipyridine copper complex to the vinyl imidazole bromide is 1:(5-50), preferably 1:(25-50), more preferably 1:(25-35), and most preferably 1:30.
[0020] Furthermore, the amount of azobisisobutyronitrile is 1%-5% of the total mass of the monomers 5,5-divinyl-2,2-bipyridine copper complex and vinyl imidazole bromide, preferably 2.5%.
[0021] Furthermore, the volume ratio of the organic solvent to deionized water is 9:1, and the volume ratio of the total mass of the 5,5-divinyl-2,2-bipyridine copper complex and vinyl imidazole bromide to the mixed solvent consisting of the organic solvent and deionized water is 1 g:10 mL.
[0022] Furthermore, the inert gas is one of nitrogen, helium and argon.
[0023] Furthermore, the pyrolysis conditions are: 600° C. for 2 hours.
[0024] The present invention also provides the use of the carbon nanotube@nitrogen-doped porous carbon-supported single-atom copper catalyst in the preparation of dimethyl carbonate by liquid-phase oxidative carbonylation of methanol. The specific application steps are as follows:
[0025] Methanol and the above-mentioned carbon nanotubes@nitrogen-doped porous carbon-supported single-atom copper catalyst are added to a high-pressure reactor to form a reaction solution, and then 2.0MPa-5.0MPa of CO and O2 mixed gas (gas pressure ratio PCO:PO2=4:1) is filled in, the reactor is sealed, and then the reaction is carried out at 110-140°C for 5-20h.
[0026] Furthermore, the content of copper (calculated as Cu element) in the reaction solution is 20-200 mmol / L.
[0027] Preferably, the temperature of the liquid phase oxidative carbonylation reaction is 110-130°C, more preferably 115-125°C.
[0028] Preferably, the pressure of the mixed gas in the liquid-phase oxidative carbonylation reaction is 3.0 MPa-5.0 MPa.
[0029] Compared with the existing multiphase copper catalysts used for the liquid phase oxidative carbonylation reaction of methanol, the catalyst provided by the present invention has the following advantages:
[0030] (1) The copper atoms in the carbon nanotube@nitrogen-doped porous carbon-supported single-atom copper catalyst prepared by the present invention are distributed in a single atom, which can greatly improve the utilization rate of copper atoms and thus improve the activity of the catalyst.
[0031] (2) The carbon nanotube@nitrogen-doped porous carbon-supported single-atom copper catalyst prepared by the present invention has a high nitrogen content, and the doped nitrogen atoms have a strong coordination ability with copper, which can enhance the electronegativity of copper atoms and is beneficial to improving the activity and stability of the catalyst.
[0032] (3) The carbon nanotube@nitrogen-doped porous carbon-supported single-atom copper catalyst prepared by the present invention presents a core-shell structure, and the nitrogen-doped porous carbon-supported single-atom copper is coated on the outer layer of the carbon nanotube with a thickness of about 1-20 nm, which is beneficial to promoting mass transfer and improving catalytic activity.
[0033] (4) During the catalyst pyrolysis process, there is no need to add activators such as KOH, which avoids post-treatment steps such as acid washing, reduces the emission of three wastes during the catalyst preparation process, and is environmentally friendly.
[0034] (5) The catalytic system has high activity, good stability, and excellent recycling performance. Under moderate temperature conditions, dimethyl carbonate can be obtained with high selectivity and high yield, and is expected to be used in actual industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is the nitrogen adsorption-desorption isotherm diagram of CNTs@NPC-Cu-1 prepared in Example 1.
[0036] Figure 2 This is the pore size distribution diagram of CNTs@NPC-Cu-1 prepared in Example 1.
[0037] Figure 3 This is the SEM image of CNTs@NPC-Cu-1 prepared in Example 1.
[0038] Figure 4 TEM image of carbon nanotubes (CNTs) used in Example 1.
[0039] Figure 5TEM image of CNTs@NPC-Cu-1 prepared in Example 1.
[0040] Figure 6 This is the HAADF-STEM image of CNTs@NPC-Cu-1 prepared in Example 1. DETAILED DESCRIPTION
[0041] The technical solution of the present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments, so as to further illustrate the technical content of the present invention.
[0042] The structural formulas of V2Br, V3Br and V6Br used in the following examples are as follows:
[0043] The preparation thereof refers to Journal of CO2 Utilization, 2022, 64, 102174.
[0044] The copper complexes used in the following examples, such as 5,5-divinyl-2,2-bipyridyl cuprous chloride and 5,5-divinyl-2,2-bipyridyl cupric acetate, were prepared according to J. Chem. Soc., Dalton Trans., 1991, 2707-2710.
[0045] The multi-walled carbon nanotubes of different specifications used in the following examples were purchased from San Chemical Technology (Shanghai) Co., Ltd.
[0046] Example 1: Carbon nanotubes@nitrogen-doped porous carbon supported single-atom copper catalyst (CNTs@NPC-Cu-1)
[0047] Take 18 ml of N,N-dimethylformamide and 2 ml of deionized water and add them to a 100 ml hydrothermal reactor. Stir evenly to form a mixed solvent. Add 0.065 g of 5,5-divinyl-2,2-bipyridyl cuprous chloride, 1.935 g of V2Br, and 0.05 g of azobisisobutyronitrile to the mixed solvent. After stirring and dissolving completely, add 0.4 g of multi-walled carbon nanotubes (specifications: inner diameter 5-10 nm, outer diameter 10-20 nm, length 0.5-2 μm, specific surface area 120 m 2 / g) and continued stirring for 30min; then, the reactor was sealed and transferred to a forced air drying oven, and the polymerization reaction was carried out at 100°C for 24 hours. After cooling to room temperature, the obtained solid was washed with anhydrous ethanol for 4 times, and then vacuum dried to obtain a nitrogen-containing porous polymer@carbon nanotube composite material. The obtained nitrogen-containing porous polymer@carbon nanotube composite material was placed in a tubular furnace, and the temperature was programmed to 600°C for pyrolysis at a heating rate of 2.5°C / min under nitrogen protection. The pyrolysis was carried out for 2 hours and cooled to room temperature to obtain a carbon nanotube@nitrogen-doped porous carbon-supported single-atom copper catalyst, which was recorded as CNTs@NPC-Cu-1.
[0048] Elemental analysis showed that the nitrogen content of CNTs@NPC-Cu-1 was 8.48wt% and the copper content was 0.24mmol / g. Figure 1 and Figure 2 They are the nitrogen adsorption and desorption isotherms and pore size distribution diagram of CNTs@NPC-Cu-1; the specific surface area of CNTs@NPC-Cu-1 is 452m 2 / g, pore volume 0.77m 3 / g; The pore size distribution of CNTs@NPC-Cu-1 is very wide, containing micropores, mesopores and macropores. Figure 3 This is the SEM image of CNTs@NPC-Cu-1. It can be seen that the prepared CNTs@NPC-Cu-1 has a tubular structure. Figure 4 , Figure 5 TEM images of carbon nanotubes and CNTs@NPC-Cu-1, respectively. It can be seen that CNTs@NPC-Cu-1 presents an obvious core-shell structure, and the thickness of the porous carbon shell is 1-8nm. XPS results show that Cu is mainly in the 0 valence state, containing a small amount of Cu + , and there is a strong interaction between Cu and nitrogen. Figure 6 This is the HAADF-STEM image of CNTs@NPC-Cu-1. Analysis shows that copper is distributed in a single atom.
[0049] Example 2: Carbon nanotubes@nitrogen-doped porous carbon supported single-atom copper catalyst (CNTs@NPC-Cu-2)
[0050] Take 18 ml of N,N-dimethylformamide and 2 ml of deionized water and add them to a 100 ml hydrothermal reactor. Stir evenly to form a mixed solvent. Add 0.182 g of 5,5-divinyl-2,2-bipyridyl cuprous chloride, 1.818 g of V2Br, and 0.05 g of azobisisobutyronitrile to the mixed solution. After stirring and dissolving completely, add 0.4 g of multi-walled carbon nanotubes (specifications: inner diameter 5-10 nm, outer diameter 10-20 nm, length 0.5-2 μm, specific surface area 120 m 2 / g) and continued stirring for 30min; then, the reactor was sealed and transferred to a forced air drying oven, and the polymerization reaction was carried out at 100°C for 24 hours. After cooling to room temperature, the obtained solid was washed with anhydrous ethanol 4 times, and then vacuum dried to obtain a nitrogen-containing porous polymer@carbon nanotube composite material. The obtained nitrogen-containing porous polymer@carbon nanotube composite material was placed in a tubular furnace, and the temperature was programmed to 600°C for pyrolysis at a heating rate of 2.5°C / min under nitrogen protection. The pyrolysis was carried out for 2 hours and cooled to room temperature to obtain a nitrogen-doped porous carbon-supported single-atom copper@carbon nanotube catalyst, which was recorded as CNTs@NPC-Cu-2.
[0051] Elemental analysis showed that the nitrogen content of CNTs@NPC-Cu-2 was 8.93wt% and the copper content was 0.59mmol / g. Nitrogen adsorption-desorption analysis showed that the specific surface area of CNTs@NPC-Cu-2 was 385m 2 / g, pore capacity 0.62m 3 / g, containing micropores, mesopores and macropores. SEM analysis shows that the prepared CNTs@NPC-Cu-2 has a tubular structure. TEM analysis shows that CNTs@NPC-Cu-2 has an obvious core-shell structure, and the thickness of the porous carbon shell is 2-11nm. XPS results show that Cu is mainly in the 0 valence state, containing a small amount of Cu + , and there is a strong interaction between Cu and nitrogen. HAADF-STEM image analysis shows that copper in CNTs@NPC-Cu-2 is distributed in a single atom.
[0052] Example 3: Carbon nanotubes@nitrogen-doped porous carbon supported single-atom copper catalyst (CNTs@NPC-Cu-3)
[0053] Take 18 ml of N,N-dimethylformamide and 2 ml of deionized water and add them to a 100 ml hydrothermal reactor. Stir evenly to form a mixed solvent. Add 0.039 g of 5,5-divinyl-2,2-bipyridyl cuprous chloride, 1.961 g of V2Br, and 0.05 g of azobisisobutyronitrile to the mixed solution. After stirring and dissolving completely, add 0.4 g of multi-walled carbon nanotubes (specifications: inner diameter 5-10 nm, outer diameter 10-20 nm, length 0.5-2 μm, specific surface area 120 m 2 / g) and continued stirring for 30min; then, the reactor was sealed and transferred to a forced air drying oven, and the polymerization reaction was carried out at 100°C for 24 hours. After cooling to room temperature, the obtained solid was washed with anhydrous ethanol for 4 times, and then vacuum dried to obtain a nitrogen-containing porous polymer@carbon nanotube composite material. The obtained nitrogen-containing porous polymer@carbon nanotube composite material was placed in a tubular furnace, and the temperature was programmed to 600°C for pyrolysis at a heating rate of 2.5°C / min under nitrogen protection. The pyrolysis was carried out for 2 hours and cooled to room temperature to obtain a nitrogen-doped porous carbon-supported single-atom copper@carbon nanotube catalyst, which was recorded as CNTs@NPC-Cu-3.
[0054] Elemental analysis shows that the nitrogen content of CNTs@NPC-Cu-3 is 7.40wt%, and the copper content is 0.16mmol / g. Nitrogen adsorption and desorption analysis shows that the specific surface area of CNTs@NPC-Cu-3 is 314m 2 / g, pore volume 0.65m 3 / g, containing micropores, mesopores and macropores. SEM analysis shows that the prepared CNTs@NPC-Cu-3 has a tubular structure. TEM analysis shows that CNTs@NPC-Cu-3 has an obvious core-shell structure, and the thickness of the porous carbon shell is 2-7nm. XPS results show that Cu is mainly in the 0 valence state, containing a small amount of Cu + , and there is a strong interaction between Cu and nitrogen. HAADF-STEM image analysis shows that copper in CNTs@NPC-Cu-3 is distributed in a single atom.
[0055] Example 4: Carbon nanotubes@nitrogen-doped porous carbon supported single-atom copper catalyst (CNTs@NPC-Cu-4)
[0056] Take 18 ml of N,N-dimethylacetamide and 2 ml of deionized water and add them to a 100 ml hydrothermal reactor. Stir evenly to form a mixed solvent. Add 0.065 g of 5,5-divinyl-2,2-bipyridyl cuprous chloride, 1.935 g of V3Br, and 0.05 g of azobisisobutyronitrile to the mixed solution. After stirring and dissolving completely, add 0.4 g of multi-walled carbon nanotubes (specifications: inner diameter 5-10 nm, outer diameter 10-20 nm, length 0.5-2 μm, specific surface area 120 m 2 / g) and continued stirring for 30min; then, the reactor was sealed and transferred to a forced air drying oven, and the polymerization reaction was carried out at 100°C for 24 hours. After cooling to room temperature, the obtained solid was washed with anhydrous ethanol for 4 times, and then vacuum dried to obtain a nitrogen-containing porous polymer@carbon nanotube composite material. The obtained nitrogen-containing porous polymer@carbon nanotube composite material was placed in a tubular furnace, and the temperature was programmed to 600°C for pyrolysis at a heating rate of 2.5°C / min under nitrogen protection. The pyrolysis was carried out for 2 hours and cooled to room temperature to obtain a nitrogen-doped porous carbon-supported single-atom copper@carbon nanotube catalyst, which was recorded as CNTs@NPC-Cu-4.
[0057] Elemental analysis shows that the nitrogen content of CNTs@NPC-Cu-4 is 8.31wt%, and the copper content is 0.22mmol / g. Nitrogen adsorption and desorption analysis shows that the specific surface area of CNTs@NPC-Cu-4 is 420m 2 / g, pore volume 0.70m 3 / g, containing micropores, mesopores and macropores. SEM analysis shows that the prepared CNTs@NPC-Cu-4 has a tubular structure. TEM analysis shows that CNTs@NPC-Cu-4 has an obvious core-shell structure, and the thickness of the porous carbon shell is 4-13nm. XPS results show that Cu is mainly in the 0 valence state, containing a small amount of Cu + , and there is a strong interaction between Cu and nitrogen. HAADF-STEM image analysis shows that copper in CNTs@NPC-Cu-4 is distributed in a single atom.
[0058] Example 5: Carbon nanotubes@nitrogen-doped porous carbon supported single-atom copper catalyst (CNTs@NPC-Cu-5)
[0059] Take 18 ml of N-methylpyrrolidone and 2 ml of deionized water and add them to a 100 ml hydrothermal reactor. Stir evenly to form a mixed solvent. Add 0.065 g of 5,5-divinyl-2,2-bipyridyl cuprous chloride, 1.935 g of V6Br, and 0.05 g of azobisisobutyronitrile to the mixed solution. After stirring and dissolving completely, add 0.4 g of multi-walled carbon nanotubes (specifications: inner diameter 5-10 nm, outer diameter 10-20 nm, length 0.5-2 μm, specific surface area 120 m 2 / g) and continued stirring for 30min; then, the reactor was sealed and transferred to a forced air drying oven, and the polymerization reaction was carried out at 100°C for 24 hours. After cooling to room temperature, the obtained solid was washed with anhydrous ethanol for 4 times, and then vacuum dried to obtain a nitrogen-containing porous polymer@carbon nanotube composite material. The obtained nitrogen-containing porous polymer@carbon nanotube composite material was placed in a tubular furnace, and the temperature was programmed to 600°C for pyrolysis at a heating rate of 2.5°C / min under nitrogen protection. The pyrolysis was carried out for 2 hours and cooled to room temperature to obtain a nitrogen-doped porous carbon-supported single-atom copper@carbon nanotube catalyst, which was recorded as CNTs@NPC-Cu-5.
[0060] Elemental analysis shows that the nitrogen content of CNTs@NPC-Cu-5 is 8.02wt%, and the copper content is 0.23mmol / g. Nitrogen adsorption and desorption analysis shows that the specific surface area of CNTs@NPC-Cu-5 is 457m 2 / g, pore volume 0.69m 3 / g, containing micropores, mesopores and macropores. SEM analysis shows that the prepared CNTs@NPC-Cu-5 has a tubular structure. TEM analysis shows that CNTs@NPC-Cu-5 has an obvious core-shell structure, and the thickness of the porous carbon shell is 3-12nm. XPS results show that Cu is mainly in the 0 valence state, containing a small amount of Cu + , and there is a strong interaction between Cu and nitrogen. HAADF-STEM image analysis shows that copper in CNTs@NPC-Cu-5 is distributed in a single atom.
[0061] Example 6: Carbon nanotubes@nitrogen-doped porous carbon supported single-atom copper catalyst (CNTs@NPC-Cu-6)
[0062] Take 18ml N,N-dimethylformamide and 2ml deionized water and add them to 100ml hydrothermal reactor, stir evenly to form a mixed solvent, add 0.065g 5,5-divinyl-2,2-bipyridyl cuprous chloride, 1.935g V2Br, and 0.05g azobisisobutyronitrile to the mixed solution, stir and dissolve completely, then add 0.2g multi-walled carbon nanotubes (specifications: inner diameter 5-10nm, outer diameter 10-20nm, length 0.5-2μm, specific surface area 120m 2 / g) and continued stirring for 30min; then, the reactor was sealed and transferred to a forced air drying oven, and the polymerization reaction was carried out at 100°C for 24 hours. After cooling to room temperature, the obtained solid was washed with anhydrous ethanol for 4 times, and then vacuum dried to obtain a nitrogen-containing porous polymer@carbon nanotube composite material. The obtained nitrogen-containing porous polymer@carbon nanotube composite material was placed in a tubular furnace, and the temperature was programmed to 600°C for pyrolysis at a heating rate of 2.5°C / min under nitrogen protection. The pyrolysis was carried out for 2 hours and cooled to room temperature to obtain a nitrogen-doped porous carbon-supported single-atom copper@carbon nanotube catalyst, which was recorded as CNTs@NPC-Cu-6.
[0063] Elemental analysis shows that the nitrogen content of CNTs@NPC-Cu-6 is 10.64wt%, and the copper content is 0.32mmol / g. Nitrogen adsorption and desorption analysis shows that the specific surface area of CNTs@NPC-Cu-6 is 574m 2 / g, pore volume 0.63m 3 / g, containing micropores, mesopores and macropores. SEM analysis shows that the prepared CNTs@NPC-Cu-6 has a tubular structure. TEM analysis shows that CNTs@NPC-Cu-6 has an obvious core-shell structure, and the thickness of the porous carbon shell is 6-18nm. XPS results show that Cu is mainly in the 0 valence state, containing a small amount of Cu + , and there is a strong interaction between Cu and nitrogen. HAADF-STEM image analysis shows that copper in CNTs@NPC-Cu-6 is distributed in a single atom.
[0064] Example 7: Carbon nanotubes@nitrogen-doped porous carbon supported single-atom copper catalyst (CNTs@NPC-Cu-7)
[0065] Take 18 ml of N,N-dimethylformamide and 2 ml of deionized water and add them to a 100 ml hydrothermal reactor. Stir evenly to form a mixed solvent. Add 0.065 g of 5,5-divinyl-2,2-bipyridyl cuprous chloride, 1.935 g of V2Br, and 0.05 g of azobisisobutyronitrile to the mixed solution. After stirring and dissolving completely, add 0.4 g of multi-walled carbon nanotubes (specifications: inner diameter 2-5 nm, outer diameter <8 nm, length 0.5-2 μm, specific surface area >350 m 2 / g) and continued stirring for 30min; then, the reactor was sealed and transferred to a forced air drying oven, and the polymerization reaction was carried out at 100°C for 24 hours. After cooling to room temperature, the obtained solid was washed with anhydrous ethanol for 4 times, and then vacuum dried to obtain a nitrogen-containing porous polymer@carbon nanotube composite material. The obtained nitrogen-containing porous polymer@carbon nanotube composite material was placed in a tubular furnace, and the temperature was programmed to 600°C for pyrolysis at a heating rate of 2.5°C / min under nitrogen protection. The pyrolysis was carried out for 2 hours and cooled to room temperature to obtain a nitrogen-doped porous carbon-supported single-atom copper@carbon nanotube catalyst, which was recorded as CNTs@NPC-Cu-7.
[0066] Elemental analysis shows that the nitrogen content of CNTs@NPC-Cu-7 is 8.55wt%, and the copper content is 0.23mmol / g. Nitrogen adsorption and desorption analysis shows that the specific surface area of CNTs@NPC-Cu-7 is 519m 2 / g, pore volume 0.73m 3 / g, containing micropores, mesopores and macropores. SEM analysis shows that the prepared CNTs@NPC-Cu-7 has a tubular structure. TEM analysis shows that CNTs@NPC-Cu-7 has an obvious core-shell structure, and the thickness of the porous carbon shell is 4-12nm. XPS results show that Cu is mainly in the 0 valence state, containing a small amount of Cu + , and there is a strong interaction between Cu and nitrogen. HAADF-STEM image analysis shows that copper in CNTs@NPC-Cu-7 is distributed in a single atom.
[0067] Example 8: Carbon nanotubes@nitrogen-doped porous carbon supported single-atom copper catalyst (CNTs@NPC-Cu-8)
[0068] Take 18 ml of N,N-dimethylformamide and 2 ml of deionized water and add them to a 100 ml hydrothermal reactor. Stir evenly to form a mixed solvent. Add 0.065 g of 5,5-divinyl-2,2-bipyridyl cuprous chloride, 1.935 g of V2Br, and 0.05 g of azobisisobutyronitrile to the mixed solution. After stirring and dissolving completely, add 0.4 g of multi-walled carbon nanotubes (specifications: inner diameter 5-15 nm, outer diameter>50 nm, length 0.5-2 μm, specific surface area>70 m 2 / g) and continued stirring for 30min; then, the reactor was sealed and transferred to a forced air drying oven, and the polymerization reaction was carried out at 100°C for 24 hours. After cooling to room temperature, the obtained solid was washed with anhydrous ethanol for 4 times, and then vacuum dried to obtain a nitrogen-containing porous polymer@carbon nanotube composite material. The obtained nitrogen-containing porous polymer@carbon nanotube composite material was placed in a tubular furnace, and the temperature was programmed to 600°C for pyrolysis at a heating rate of 2.5°C / min under nitrogen protection. The pyrolysis was carried out for 2 hours and cooled to room temperature to obtain a nitrogen-doped porous carbon-supported single-atom copper@carbon nanotube catalyst, which was recorded as CNTs@NPC-Cu-8.
[0069] Elemental analysis shows that the nitrogen content of CNTs@NPC-Cu-8 is 8.49wt%, and the copper content is 0.24mmol / g. Nitrogen adsorption and desorption analysis shows that the specific surface area of CNTs@NPC-Cu-8 is 391m 2 / g, pore volume 0.54m 3 / g, containing micropores, mesopores and macropores. SEM analysis shows that the prepared CNTs@NPC-Cu-8 has a tubular structure. TEM analysis shows that CNTs@NPC-Cu-8 has an obvious core-shell structure, and the thickness of the porous carbon shell is 2-7nm. XPS results show that Cu is mainly in the 0 valence state, containing a small amount of Cu + , and there is a strong interaction between Cu and nitrogen. HAADF-STEM image analysis shows that copper in CNTs@NPC-Cu-8 is distributed in a single atom.
[0070] Example 9: Carbon nanotubes@nitrogen-doped porous carbon supported single-atom copper catalyst (CNTs@NPC-Cu-9)
[0071] Take 18 ml of N,N-dimethylformamide and 2 ml of deionized water and add them to a 100 ml hydrothermal reactor. Stir evenly to form a mixed solvent. Add 0.065 g of 5,5-divinyl-2,2-bipyridyl cuprous chloride, 1.935 g of V2Br, and 0.05 g of azobisisobutyronitrile to the mixed solution. After stirring and dissolving completely, add 0.4 g of multi-walled carbon nanotubes (specifications: inner diameter 5-15 nm, outer diameter 10-20 nm, length 10-30 μm, specific surface area>150 m 2 / g) and continued stirring for 30min; then, the reactor was sealed and transferred to a forced air drying oven, and the polymerization reaction was carried out at 100°C for 24 hours. After cooling to room temperature, the obtained solid was washed with anhydrous ethanol for 4 times, and then vacuum dried to obtain a nitrogen-containing porous polymer@carbon nanotube composite material. The obtained nitrogen-containing porous polymer@carbon nanotube composite material was placed in a tubular furnace, and the temperature was programmed to 600°C for pyrolysis at a heating rate of 2.5°C / min under nitrogen protection. The pyrolysis was carried out for 2 hours and cooled to room temperature to obtain a nitrogen-doped porous carbon-supported single-atom copper@carbon nanotube catalyst, which was recorded as CNTs@NPC-Cu-9.
[0072] Elemental analysis shows that the nitrogen content of CNTs@NPC-Cu-9 is 8.76wt%, and the copper content is 0.23mmol / g. Nitrogen adsorption and desorption analysis shows that the specific surface area of CNTs@NPC-Cu-9 is 426m 2 / g, pore volume 0.67m 3 / g, containing micropores, mesopores and macropores. SEM analysis shows that the prepared CNTs@NPC-Cu-9 has a tubular structure. TEM analysis shows that CNTs@NPC-Cu-9 has an obvious core-shell structure, and the thickness of the porous carbon shell is 2-9nm. XPS results show that Cu is mainly in the 0 valence state, containing a small amount of Cu + , and there is a strong interaction between Cu and nitrogen. HAADF-STEM image analysis shows that copper in CNTs@NPC-Cu-9 is distributed in a single atom.
[0073] Example 10: Carbon nanotubes@nitrogen-doped porous carbon supported single-atom copper catalyst (CNTs@NPC-Cu-10)
[0074] Take 18 ml of N,N-dimethylformamide and 2 ml of deionized water and add them to a 100 ml hydrothermal reactor. Stir evenly to form a mixed solvent. Add 0.065 g of 5,5-divinyl-2,2-bipyridyl copper acetate, 1.935 g of V2Br, and 0.05 g of azobisisobutyronitrile to the mixed solution. After stirring and dissolving completely, add 0.4 g of multi-walled carbon nanotubes (specifications: inner diameter 5-10 nm, outer diameter 10-20 nm, length 0.5-2 μm, specific surface area 120 m 2 / g) and continued stirring for 30min; then, the reactor was sealed and transferred to a forced air drying oven, and the polymerization reaction was carried out at 100°C for 24 hours. After cooling to room temperature, the obtained solid was washed with anhydrous ethanol 4 times, and then vacuum dried to obtain a nitrogen-containing porous polymer@carbon nanotube composite material. The obtained nitrogen-containing porous polymer@carbon nanotube composite material was placed in a tubular furnace, and the temperature was programmed to 600°C for pyrolysis at a heating rate of 2.5°C / min under nitrogen protection. The pyrolysis was carried out for 2 hours and cooled to room temperature to obtain a nitrogen-doped porous carbon-supported single-atom copper@carbon nanotube catalyst, which was recorded as CNTs@NPC-Cu-10.
[0075] Elemental analysis shows that the nitrogen content of CNTs@NPC-Cu-10 is 8.17wt%, and the copper content is 0.25mmol / g. Nitrogen adsorption and desorption analysis shows that the specific surface area of CNTs@NPC-Cu-10 is 479m 2 / g, pore volume 0.75m 3 / g, containing micropores, mesopores and macropores. SEM analysis shows that the prepared CNTs@NPC-Cu-10 has a tubular structure. TEM analysis shows that CNTs@NPC-Cu-10 has an obvious core-shell structure, and the thickness of the porous carbon shell is 2-8nm. XPS results show that Cu is mainly in the +1 valence state, containing a small amount of Cu 0 and Cu 2+ , and there is a strong interaction between Cu and nitrogen. HAADF-STEM image analysis shows that copper in CNTs@NPC-Cu-10 is distributed in a single atom.
[0076] Example 11: Nitrogen-doped porous carbon supported single atom copper catalyst (NPC-Cu)
[0077] 18 ml of N,N-dimethylformamide and 2 ml of deionized water were added to a 100 ml hydrothermal reactor, stirred evenly to form a mixed solvent, 0.065 g of 5,5-divinyl-2,2-bipyridyl cuprous chloride, 1.935 g of V2Br, and 0.05 g of azobisisobutyronitrile were added to the mixed solution, and after stirring and dissolving completely, the reactor was sealed and transferred to a forced air drying oven, and the polymerization reaction was carried out at 100 ° C for 24 hours. After cooling to room temperature, the obtained solid was washed with anhydrous ethanol 4 times, and then vacuum dried to obtain a nitrogen-containing porous polymer material. The obtained nitrogen-containing porous polymer material was placed in a tubular furnace, and the temperature was raised to 600 ° C at a heating rate of 2.5 ° C / min under nitrogen protection for pyrolysis, pyrolysis for 2 hours, and cooled to room temperature to obtain a nitrogen-doped porous carbon-supported single-atom copper catalyst, which was recorded as NPC-Cu.
[0078] Elemental analysis shows that the nitrogen content of NPC-Cu is 15.26wt%, and the copper content is 0.42mmol / g. Nitrogen adsorption and desorption analysis shows that the specific surface area of NPC-Cu is 782m 2 / g, pore volume 0.66m 3 / g, containing micropores, mesopores and macropores. SEM and TEM analysis showed that the prepared NPC-Cu presented an irregular particle structure. XPS results showed that Cu was mainly in the 0 valence state, containing a small amount of Cu + , and there is a strong interaction between Cu and nitrogen. HAADF-STEM image analysis shows that copper in NPC-Cu is distributed in a single atom.
[0079] Example 12: Preparation of dimethyl carbonate by oxidative carbonylation of methanol catalyzed by CNTs@NPC-Cu-1
[0080] The catalyst CNTs@NPC-Cu-1 prepared in Example 1 was used for the oxidative carbonylation reaction of methanol to prepare dimethyl carbonate. The specific steps are as follows: 20 ml of anhydrous methanol and 4.17 g of CNTs@NPC-Cu-1 catalyst were added as reaction solution in a 100 ml high-pressure reactor (the concentration of Cu in the reaction solution was 50 mmol / L), and then 3.0 MPa of CO and O2 mixed gas (PCO:PO2=4:1) was filled in. The reactor was sealed and reacted at 120°C for 6 hours. After the reaction, the reactor was cooled to room temperature, the catalyst was filtered out, and a solution containing the product dimethyl carbonate was obtained. The solution was quantitatively analyzed by gas chromatography, and the yield of dimethyl carbonate was 35.1%, and the selectivity of dimethyl carbonate was 99.8%.
[0081] After the reaction, the catalyst was filtered, washed with methanol for 3 times, and vacuum dried at 60°C for 12 hours, and then reacted under the same conditions as the above application performance test to test its recycling performance. This was a two-cycle experiment, and then the same 28 cycles were performed, for a total of 30 times. The dimethyl carbonate yield results of each cycle experiment are shown in Table 1 below. After 30 cycles of CNTs@NPC-Cu-1, the dimethyl carbonate yield remained above 34.2%, and the dimethyl carbonate selectivity detected was greater than 99.6%.
[0082] Table 1
[0083]
[0084] Example 13: Preparation of dimethyl carbonate by oxidative carbonylation of methanol catalyzed by CNTs@NPC-Cu-1
[0085] The reaction temperature was replaced from 120° C. to 100° C., and the other conditions and parameters were consistent with those in Example 12. The yield of dimethyl carbonate was 7.1% and the selectivity was 99.7%.
[0086] The reaction pressure was replaced from 3 MPa to 5 MPa, and the other conditions and parameters were consistent with those in Example 12. The yield of dimethyl carbonate was 36.2% and the selectivity was 99.8%.
[0087] The reaction temperature was changed from 120°C to 130°C, and the amount of CNTs@NPC-Cu-1 catalyst was changed from 4.17g to 2.09g. The yield of dimethyl carbonate was 33.5% and the selectivity was 98.4%.
[0088] Example 14: Preparation of dimethyl carbonate by oxidative carbonylation of methanol catalyzed by other catalysts
[0089] 4.17 g of CNTs@NPC-Cu-1 catalyst (copper content: 0.24 mmol / g) was replaced with 1.70 g of CNTs@NPC-Cu-2 catalyst (copper content: 0.59 mmol / g), and the concentration of Cu in the reaction solution was maintained at 50 mmol / L. The other conditions and parameters were consistent with those in Example 12. The yield of dimethyl carbonate was 17.4% and the selectivity was 99.7%.
[0090] 4.17 g of CNTs@NPC-Cu-1 catalyst (copper content: 0.24 mmol / g) was replaced with 6.26 g of CNTs@NPC-Cu-3 catalyst (copper content: 0.16 mmol / g), and the concentration of Cu in the reaction solution was maintained at 50 mmol / L. The other conditions and parameters were consistent with those in Example 12. The yield of dimethyl carbonate was 24.9% and the selectivity was 99.6%.
[0091] 4.17 g of CNTs@NPC-Cu-1 catalyst (copper content: 0.24 mmol / g) was replaced with 4.55 g of CNTs@NPC-Cu-4 catalyst (copper content: 0.22 mmol / g), and the concentration of Cu in the reaction solution was maintained at 50 mmol / L. The other conditions and parameters were consistent with those in Example 12. The yield of dimethyl carbonate was 29.0% and the selectivity was 99.8%.
[0092] 4.17 g of CNTs@NPC-Cu-1 catalyst (copper content: 0.24 mmol / g) was replaced with 4.35 g of CNTs@NPC-Cu-5 catalyst (copper content: 0.23 mmol / g), and the concentration of Cu in the reaction solution was maintained at 50 mmol / L. The other conditions and parameters were consistent with those in Example 12. The yield of dimethyl carbonate was 31.2% and the selectivity was 99.7%.
[0093] 4.17 g of CNTs@NPC-Cu-1 catalyst (copper content: 0.24 mmol / g) was replaced with 3.13 g of CNTs@NPC-Cu-6 catalyst (copper content: 0.32 mmol / g), and the concentration of Cu in the reaction solution was maintained at 50 mmol / L. The other conditions and parameters were consistent with those in Example 12. The yield of dimethyl carbonate was 14.8% and the selectivity was 99.5%.
[0094] 4.17 g of CNTs@NPC-Cu-1 catalyst (copper content: 0.24 mmol / g) was replaced with 4.35 g of CNTs@NPC-Cu-7 catalyst (copper content: 0.23 mmol / g), and the concentration of Cu in the reaction solution was maintained at 50 mmol / L. The other conditions and parameters were consistent with those in Example 12. The yield of dimethyl carbonate was 23.2% and the selectivity was 99.8%.
[0095] 4.17 g of CNTs@NPC-Cu-1 catalyst (copper content: 0.24 mmol / g) was replaced with 4.17 g of CNTs@NPC-Cu-8 catalyst (copper content: 0.24 mmol / g), and the concentration of Cu in the reaction solution was maintained at 50 mmol / L. The other conditions and parameters were consistent with those in Example 12. The yield of dimethyl carbonate was 28.1% and the selectivity was 99.6%.
[0096] 4.17 g of CNTs@NPC-Cu-1 catalyst (copper content: 0.24 mmol / g) was replaced with 4.35 g of CNTs@NPC-Cu-9 catalyst (copper content: 0.23 mmol / g), and the concentration of Cu in the reaction solution was maintained at 50 mmol / L. The other conditions and parameters were consistent with those in Example 12. The yield of dimethyl carbonate was 25.5% and the selectivity was 99.8%.
[0097] 4.17 g of CNTs@NPC-Cu-1 catalyst (copper content: 0.24 mmol / g) was replaced with 4.00 g of CNTs@NPC-Cu-10 catalyst (copper content: 0.25 mmol / g), and the concentration of Cu in the reaction solution was maintained at 50 mmol / L. The other conditions and parameters were consistent with those in Example 12. The yield of dimethyl carbonate was 21.6% and the selectivity was 99.5%.
[0098] 4.17 g of CNTs@NPC-Cu-1 catalyst (copper content: 0.24 mmol / g) was replaced with 2.38 g of NPC-Cu catalyst (copper content: 0.42 mmol / g), and the concentration of Cu in the reaction solution was maintained at 50 mmol / L. The other conditions and parameters were consistent with those in Example 12. The yield of dimethyl carbonate was 8.2% and the selectivity was 99.5%.
[0099] From this we can see that:
[0100] The activity of CNTs@NPC-Cu-1 catalyst is significantly better than that of NPC-Cu catalyst. The reason is that the carbon nanotubes in the core-shell structured carbon nanotubes@nitrogen-doped porous carbon-supported single-atom copper catalyst affect mass transfer and have a great influence on the reaction activity.
[0101] The activity of CNTs@NPC-Cu-1 catalyst is significantly better than that of CNTs@NPC-Cu-6 catalyst, because the porous carbon shell thickness of CNTs@NPC-Cu-6 catalyst prepared by halving the amount of multi-walled carbon nanotubes added is relatively thick, which affects mass transfer. Therefore, the mass ratio of the multi-walled carbon nanotubes to the total mass of the monomer 5,5-divinyl-2,2-bipyridine copper complex and vinyl imidazole bromide should not be less than 1:10.
[0102] From the comparison of the activities of CNTs@NPC-Cu-1 catalyst, CNTs@NPC-Cu-7 catalyst, CNTs@NPC-Cu-8 catalyst and CNTs@NPC-Cu-9 catalyst, it can be seen that the inner diameter of the multi-walled carbon nanotubes is 2-20nm, the outer diameter is 6-80nm, and the length is 0.5-30μm. The performance of the prepared CNTs@NPC-Cu-6 catalyst is excellent. Within this range, if the inner and outer diameters of the multi-walled carbon nanotubes are too small or too large, it will to a certain extent lead to a thicker thickness of the porous carbon shell layer in the prepared CNTs@NPC-Cu catalyst, and the mass transfer will be hindered; if the multi-walled carbon nanotubes are too long, the mass transfer resistance will also be relatively large.
[0103] The activity of CNTs@NPC-Cu-1 catalyst is better than that of CNTs@NPC-Cu-10 catalyst. The reason is that for this type of carbonylation reaction, CuCl is generally better than copper acetate, and the monovalent CuCl is better than the divalent CuCl.
Claims
1. A carbon nanotube@nitrogen-doped porous carbon supported single-atom copper catalyst, characterized in that: Prepared by the following method: A certain amount of organic solvent and deionized water are added to a reactor, a certain amount of 5,5-divinyl-2,2-bipyridine copper complex, vinyl imidazole bromide, and azobisisobutyronitrile are added to the obtained mixed solvent, and after stirring and dissolving, multi-walled carbon nanotubes are added, and the mixture is stirred evenly; then, the reactor is sealed, and the reactor is placed at 80-140° C. for polymerization reaction for 12-48 hours, cooled, washed, and vacuum dried to obtain a nitrogen-containing porous polymer@carbon nanotube composite material; The obtained nitrogen-containing porous polymer@carbon nanotube composite material is heated to 550-700°C under the protection of an inert gas for pyrolysis, and then cooled to room temperature to obtain a carbon nanotube@nitrogen-doped porous carbon-supported single-atom copper catalyst; The ratio of the mass of the multi-walled carbon nanotubes to the total mass of the 5,5-divinyl-2,2-bipyridine copper complex and the vinyl imidazole bromide is 1:(1-10), preferably 1:(4-6), and more preferably 1:
5.
2. The catalyst according to claim 1, characterized in that The multi-walled carbon nanotube has an inner diameter of 2-20nm, an outer diameter of 6-80nm, and a length of 0.5-30μm. Preferably, the multi-walled carbon nanotube has an inner diameter of 5-15nm, an outer diameter of 10-20nm, and a length of 0.5-2μm. More preferably, the multi-walled carbon nanotube has an inner diameter of 5-10nm, an outer diameter of 10-20nm, and a length of 0.5-2μm.
3. The catalyst according to claim 2, characterized in that The mass ratio of the 5,5-divinyl-2,2-bipyridine copper complex to the vinyl imidazole bromide is 1:(5-50), preferably 1:(25-50), more preferably 1:(25-35), and most preferably 1:
30.
4. The catalyst according to any one of claims 1 to 3, characterized in that The structural formula of the 5,5-divinyl-2,2-bipyridine copper complex is as follows: In the structural formula, Cu is +1 or +2, and X is Cl. - Br - ,I - 、CH3COO - Any one of .
5. The catalyst according to claim 4, characterized in that The vinyl imidazole bromide is any one of V2Br, V3Br, and V6Br, and its structure is as follows:
6. The catalyst according to any one of claims 1 to 3, characterized in that The organic solvent is one of N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone.
7. The catalyst according to any one of claims 1 to 3, characterized in that The dosage of azobisisobutyronitrile is 1%-5% of the total mass of 5,5-divinyl-2,2-bipyridine copper complex and vinyl imidazole bromide.
8. Use of the carbon nanotube@nitrogen-doped porous carbon supported single-atom copper catalyst according to any one of claims 1 to 7 in the preparation of dimethyl carbonate by liquid-phase oxidative carbonylation of methanol.
9. The use according to claim 8, characterized in that: The specific steps of the application are as follows: Methanol and the carbon nanotube@nitrogen-doped porous carbon-supported single-atom copper catalyst according to any one of claims 1 to 7 are added to a high-pressure reactor to form a reaction liquid, and then a mixed gas of CO and O2 at 2.0MPa-5.0MPa is filled in, the reactor is sealed, and then the reaction is carried out at 110-140°C for 5-20h, and the copper content in the reaction liquid is 20-200mmol / L.
10. The use according to claim 9, characterized in that: The pressure ratio of the CO and O2 mixed gas is PCO:PO2=4:1.
Citation Information
Patent Citations
Quick preparation method of core-shell type carbon cladding nano copper catalyst
CN104324757A
Preparation method of nitrogen-doped graphene and nitrogen-doped graphene loaded nanocrystalline catalyst
CN105293484A
Preparation method of copper-doped graphene catalyst
CN107262095A
Preparation method and application of Cu / N doped carbon nanosheet catalyst with high stability
CN111974435A